2017
DOI: 10.2106/jbjs.rvw.17.00030
|View full text |Cite
|
Sign up to set email alerts
|

Team Approach: Osteosarcoma of the Distal Part of the Femur in Adolescents

Abstract: Osteosarcoma, while rare, is the most common primary bone cancer and accounts for up to 10% of all new pediatric cancer diagnoses annually in the United States. Most commonly, osteosarcoma affects the distal femur and occurs as a high-grade intramedullary (conventional) subtype. Patients with osteosarcoma are treated with a multi-disciplinary team approach.1 Often, an orthopaedic oncologist initiates the workup after making a presumptive diagnosis based on classic clinical and radiographic findings. Advanced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…3 Osteosarcoma has a predilection for invading the metaphysis of the long bones of the appendicular skeleton, chiefly the distal femur and proximal tibia. 4 Osteosarcoma can also affect the axial skeleton/other locations, although this is less common. 4…”
mentioning
confidence: 99%
“…3 Osteosarcoma has a predilection for invading the metaphysis of the long bones of the appendicular skeleton, chiefly the distal femur and proximal tibia. 4 Osteosarcoma can also affect the axial skeleton/other locations, although this is less common. 4…”
mentioning
confidence: 99%
“…In fact, it is not surprising that conventional MR images could be informative (to a certain extent) in approximating the degree of tumor necrosis. Researchers have shown that visual interpretations of conventional MR images are indeed possible for the prognosis of osteosarcoma [ 10 , 51 , 52 ]. First, intraosseous (intramedullary) tumor is evident on T1-weighted MR images as areas of low signal intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with musculoskeletal tumors are usually treated with a multidisciplinary approach 25,26 . At the first visit, patients may be referred to orthopedists, oncologists, or radiologists.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with musculoskeletal tumors are usually treated with a multidisciplinary approach. 25,26 At the first visit, patients may be referred to orthopedists, oncologists, or radiologists. However, it is difficult for physicians to develop sufficient experience in diagnosing musculoskeletal tumors due to its rarity.…”
Section: Discussionmentioning
confidence: 99%